Situation Report: Bulgaria, 11 September 1969 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. Celebration of September 9 Clemency for Prisoners and Cancellation of Some Debts Meeting of Politburo Members and Komsomol Activists Party Decree on Sports Bulgaria and Ho Chi Minh's Death